2008
DOI: 10.1016/j.chembiol.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antifungal Polyene Macrolides via Engineering of the Nystatin Biosynthetic Genes in Streptomyces noursei

Abstract: Seven polyene macrolides with alterations in the polyol region and exocyclic carboxy group were obtained via genetic engineering of the nystatin biosynthesis genes in Streptomyces noursei. In vitro analyses of the compounds for antifungal and hemolytic activities indicated that combinations of several mutations caused additive improvements in their activity-toxicity properties. The two best analogs selected on the basis of in vitro data were tested for acute toxicity and antifungal activity in a mouse model. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 33 publications
3
63
0
5
Order By: Relevance
“…"post-assembly oxidation"), приводила к образованию аналогов нистатина (рис. 4) с улучшенными противогрибковыми свойствами и меньшей токсичностью [34]. Инактивация post-PKS P450, который окисляет метильную группу в нистатине до карбоксильной (по С16), сопряжённая с мутацией еноил-редуктазной активности в NysC PKS модуле, приводила к образованию метильного производного с конъюгированной гептаеновой частью (в противоположность прерванному гексаену).…”
Section: примечание переводчика * лантионин -редко встречающаяся в прunclassified
“…"post-assembly oxidation"), приводила к образованию аналогов нистатина (рис. 4) с улучшенными противогрибковыми свойствами и меньшей токсичностью [34]. Инактивация post-PKS P450, который окисляет метильную группу в нистатине до карбоксильной (по С16), сопряжённая с мутацией еноил-редуктазной активности в NysC PKS модуле, приводила к образованию метильного производного с конъюгированной гептаеновой частью (в противоположность прерванному гексаену).…”
Section: примечание переводчика * лантионин -редко встречающаяся в прunclassified
“…1) is a medically important antifungal antibiotic, and it was recently shown that nystatin analogues with high antifungal activity and lower toxicity can be obtained via manipulation of the nystatin biosynthetic genes (7). Among the envisaged analogues that would be interesting to produce and analyze are those that would contain an extended or modified C-37 side chain resulting from the initiation of biosynthesis with a starting unit other than acetate.…”
mentioning
confidence: 99%
“…The same compound has been synthesised by chemical modification of amphotericin B, but this approach is less efficient (Palacios et al, 2007). A nystatin heptaene counterpart of this analogue is biosynthesised at yields of 0.5 g/litre and is superior to amphotericin B in animal models of candidiasis (Brautaset et al, 2008).…”
Section: Production Of Polyene Analogues By Chemical and Biological Mmentioning
confidence: 99%
“…This gene has been inactivated in the producers of amphotericin B, nystatin, candicidin, and rimocidin (Caffrey et al, 2008;Brautaset et al, 2008;Chen et al, 2009). In all cases, replacing the exocyclic carboxyl group with a methyl group decreases haemolytic activity but not antifungal activity.…”
Section: Engineering Late Modifications Of Polyene Macrolactone Ringsmentioning
confidence: 99%